PERSPEKTIF GENDER DALAM NOVEL KARTINI KARYA ABIDAH EL KHALIEQY DAN RELEVANSINYA DENGAN PENGEMBANGAN PEMBELAJARAN SASTRA - Khairani, Zuraida; Marisya, Susanti; Fitriani, Novi (STKIP Pesisir Selatan, 2025)
Literature learning is a means to provide students with an understanding of gender perspectives. This study aims to describe the forms of gender discrimination that occur in the Kartini novel by Adibah El Khalieqy (2) The relevance of gender perspective studies to literature learning at the secondary school level. This study is a qualitative descriptive study with data collection techniques in the form of reading and note-taking techniques. The data source used in this study is the literary work of the Kartini novel by Adibah El Khalieqy. Data in the form of words, phrases, clauses, sentences containing statements of gender discrimination in the Kartini novel by Adibah El Khalieqy. Results The results of the study show that 1) Gender discrimination generally occurs in all female characters in the novel. Ngasirah (Kartini's biological mother), Kartini, and Kardinah. Forms of gender discrimination include marginalization, subornation, stereotypes, and violence. 2) The study of feminism in the Kartini novel regarding gender perspective is quite relevant to literature learning at the secondary school level with the Brainstorming learning method.